From feminist critique to gender mainstreaming — and back? The case of German urban planning. Issue 7 (2nd July 2020) - Huning, Sandra
Abstract: In spatial planning debates in Germany and other European countries, a discursive turn from feminist planning critique to gender planning over the past 20 years has led to ambiguous results. On the one hand, feminist claims have been translated into guidelines and criteria catalogues which help planners to consider them in their professional practice. On the other hand, this approach to gender mainstreaming has not made it any easier in planning practice to address (gendered) power relations and their spatial expressions. A gap between professional practice and academic debate has emerged in spite of feminists' conviction that theory and practice are interrelated. This paper presents this argument with a particular focus on gender planning in Germany, and three options how to go on: a target-group approach oriented towards equal opportunities, a deconstructive approach looking to overcome discriminatory practice and a performative approach. As a consequence, this paper proposes a diversification of strategies both in professional practice and in academic research in order to reconcile different rationales and theoretical concepts that are used in gender studies, planning theory and practice.